PENGEMBANGAN KARAKTER RASA TANGGUNGJAWAB MENGGUNAKAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) PADA MAHASISWA TINGKAT I PROGRAM STUDI PGSD FKIP UNIVERSITAS NUSANTARA PGRI KEDIRI - Soenarko, Bambang; Mujiwati, Endang Sri (Universitas Nusantara PGRI Kediri, 2016)
Today the life of the Indonesian people to experience a shift in values. This condition is then said to moral decadence, which marked the rise of crime and deviant behavior, the perpetrator of the younger generation, in addition to children and parents, even with the title of community leaders and officials. Increasingly felt moral decline to a level that is quite disturbing classified as